Homelessness and Mortality Among Persons With Tuberculosis in Texas, 2010-2017 - Agarwal, Saroochi (Public Health Rep, 2019)
OBJECTIVE: A disproportionate number of tuberculosis cases and tuberculosis deaths occur among persons experiencing homelessness in the United States. Our objective was to identify risks for homelessness and death during mycobacterial treatment among persons experiencing homelessness with tuberculosis in Texas. METHODS: Using data from the Centers for Disease Control and Prevention’s TB Genotyping Information Management System, we evaluated data on demographic, laboratory, and clinical characteristics of persons experiencing homelessness in Texas during the year before tuberculosis diagnosis, from January 1, 2010, through December 31, 2017. RESULTS: Of 10 130 new diagnoses of tuberculosis among persons living in Texas during the study period, 543 were reported as being homeless in the year before tuberculosis diagnosis. The odds of dying during treatment were 2.26 (95% confidence interval, 1.68-3.03) times higher among persons with tuberculosis experiencing homelessness than among persons with tuberculosis living in homes. CONCLUSIONS: Our findings indicate that persons experiencing homelessness bear an undue burden of tuberculosis mortality in Texas. The burden may be related to poorer health caused by poverty stressors, comorbidities, or lack of access to health care.